2016
DOI: 10.1155/2016/2095195
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Analysis of Alfalfa Seedlings Response to Acid-Aluminum

Abstract: Acid-Aluminum (Al) is toxic to plants and greatly affects crop production worldwide. To understand the responses of plants to acid soils and Aluminum toxicity, we examined global gene expression using microarray data in alfalfa seedlings with the treatment of acid-Aluminum. 3,926 genes that were identified significantly up- or downregulated in response to Al3+ ions with pH 4.5 treatment, 66.33% of which were found in roots. Their functional categories were mainly involved with phytohormone regulation, reactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 43 publications
2
18
0
Order By: Relevance
“…Meanwhile, CA10g12810 , which is homologous to Arabidopsis thaliana APL , also encodes a MYB-family TF APL predicted to participate in the regulation of anthocyanin metabolism (GO:0031537). Further, Zhou et al (2016) reported that APL was also involved in phenylpropanoid and flavonoid biosynthesis pathways [ 52 ]. CA10g12710 , a homolog of nol10 in Danio rerio was predicted to be a WD40 repeat protein based on its COG annotation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, CA10g12810 , which is homologous to Arabidopsis thaliana APL , also encodes a MYB-family TF APL predicted to participate in the regulation of anthocyanin metabolism (GO:0031537). Further, Zhou et al (2016) reported that APL was also involved in phenylpropanoid and flavonoid biosynthesis pathways [ 52 ]. CA10g12710 , a homolog of nol10 in Danio rerio was predicted to be a WD40 repeat protein based on its COG annotation.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we may answer the question rasied by Zhang et al (2015) that MYB39 might take part in phenylpropanoid pathway [ 75 ]. Zhou et al (2016) also reported that APL took part in phenylpropanoid and flavonoid biosynthesis pathways [ 52 ]. CA10g03650 and CA10g12810 were different from A locus because A locus was homologous to tomato ANT1 and petunia AN2 [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Al toxicity severely restricts the growth of alfalfa. In our previous study of transcriptome‐wide analysis of Al‐stressed alfalfa seedlings, six LEA genes were found to be upregulated under Al stress (Zhou et al., 2016). Upon overexpressing the LEA genes in Arabidopsis, abiotic stress (drought, salt and Al) tests showed that an SK 3 ‐type DHN MsDHN1 significantly increased the Al tolerance of transgenic Arabidopsis.…”
Section: Introductionmentioning
confidence: 97%
“…MYB and NAC TFs were majorly involved in the tolerance mechanism in the case of cultivars, whereas in the case of wild, WRKY and bHLH TFs were majorly involved. Zhou et al ( 2016 ) found that MYB and WRKY TFs were involved in the regulation of ROS and flavonoid biosynthesis under Al 3+ stress conditions in alfalfa. Similarly, zinc finger, MYB, and WRKY TFs, together, played critical roles in Al 3+ stress resilience in tea (Huang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%